Torture : a collection - Levinson, Sanford, 1941- (OUP E-Books., 2004)
Torture is perhaps the most unequivocally banned practice in the world today. Yet recent photographs from Abu Ghraib substantiated claims that the United States and some of its allies are using methods of questioning relating to the war on terrorism that could be described as torture or, at the very least, as inhuman and degrading. In terror's wake, the use of such methods, at least under some conditions, has gained some prominent defenders, notably from within the White House. In this revised edition, Torture: A Collection brings together leading lawyers, political theorists, social scientists, and public intellectuals to debate the advisability of maintaining the absolute ban and to reflect on what it says about our societies if we do--or do not--adhere to it in all circumstances. New to this edition are essays by Charles Krauthammer and Andrew Sullivan on the adoption in 2005 of the McCain Amendment, which explicitly bars the use of torture and other cruel methods of interrogation.